Final Analysis of the Magnetic Resonance Imaging in Active Surveillance Trial. Issue 5 (10th November 2022) - Doan, Paul; Scheltema, Matthijs J.; Amin, Amer; Shnier, Ron; Geboers, Bart; Gondoputro, William; Moses, Daniel; van Leeuwen, Pim J.; Haynes, Anne Maree; Matthews, Jayne; Brenner, Phillip; O'Neill, Gordon; et al.
Abstract : Purpose: This study aimed to assess the medium-term oncologic outcomes of an active surveillance protocol, replacing confirmatory biopsy with serial multiparametric magnetic resonance imaging. Materials and Methods: A total of 172 men were enrolled in this single-arm prospective trial. Men with prostate cancer (Gleason 3+3=6 or Gleason 3+4=7 with ≤10% Gleason pattern 4 overall and <2 cores Gleason pattern 4) eligible for surveillance were included in the study. Men underwent baseline multiparametric magnetic resonance imaging and template ± targeted biopsy, then multiparametric magnetic resonance imaging at years 1 and 2 with a 3-year end-of-protocol biopsy. Biopsies during the 3-year protocol period were triggered by abnormalities on multiparametric magnetic resonance imaging and/or increases in prostate specific antigen density (>0.2 ng/ml/cc). Results: The sensitivity, specificity, positive predictive value, and negative predictive value of multiparametric magnetic resonance imaging to detect progression to clinically significant prostate cancer were 57% (95% CI 39%-74%), 82% (95% CI 74%-89%), 50% (95% CI 38%-62%), and 86% (95% CI 81%-90%), respectively. Both multiparametric magnetic resonance imaging and prostate specific antigen density were significant predictors for progression (multiparametric magnetic resonance imaging OR 6.20, 95% CI 2.72-14.16, P < .001; prostate specific antigen density OR 6.19, 95% CI 2.14-17.92, P = .001). Only 2.3% (4/172) of patients had false-negative multiparametric magnetic resonance imaging and high-risk pathological features (pT3 or high-volume International Society of Urological Pathology >2). After a median 69 months (Q1-Q3 56-79) follow-up of all patients in the cohort, freedom from biochemical recurrence, metastasis, and prostate cancer–related death were 99.3%, 100%, and 100%, respectively. Conclusions: Final analysis of the Magnetic Resonance Imaging in Active Surveillance trial indicates that there is minimal risk to omitting 1-year confirmatory biopsy during active surveillance if baseline magnetic resonance–targeted + saturation template biopsy was performed; however, standardized 3-year systematic biopsy should be performed due to occasional magnetic resonance imaging–invisible tumors.